PREVALENCE, PATTERN AND CORRELATES OF STUDY DIFFICULTY AMONG STUDENTS OF COLLEGE OF HEALTH SCIENCES LADOKE AKINTOLA UNIVERSITY OF TECHNOLOGY OSOGBO. - Falade, J.; Eegunranti, B. A.; Tobih, J. E.; Ogundiran, A. C.; Ibigbami, O.; Akinsulore, A.; Ogundiran, O. (Advances in Social Sciences Research Journal, 2019)
Introduction - Study difficulty is the inability to obtain maximum result from efforts put into studying. It can negatively affect the physical and mental stability of the student leading to increased dropout from school. Objective - This study examined the prevalence, pattern and correlates of study difficulty among students of College of Health Sciences, Ladoke Akintola University of Technology Osogbo. Methods - Two hundred and seventy-seven students of the College were consecutively recruited. Each student filled socio-demographic questionnaire, University College London Study Questionnaire (UCLSQ), Brief COPE Questionnaire and General Health Questionnaire. The Statistical Package for Social Science (SPSS) software (version 21) was used for the analysis. Results -The mean age of the respondents was 26.3 years. The proportion of Medical, Nursing and Medical Laboratory Science students were 42.6%, 31.8% and 25.6%respectively. Most of the respondents were from married home (77.5%), monogamous setting (78.0%), parents with tertiary education and higher class of occupation. The prevalence of study difficulty among the respondents was 52.0%. Multiple linear regression analysis with stepwise method showed that respondents using less of adaptive coping strategies (p = 0,005) and presence of psychiatric morbidity (p<0.001) were independently associated with the presence of study difficulty. Conclusion - This study has shown that psychiatric morbidity and maladaptive coping strategy use were more common among students with study difficulty. A routine mental health assessment and practical teaching of adaptive coping strategy in the citadels of learning in particular the tertiary level/medical and paramedical professions.